ASEAN membership expansion, spatial construction and ASEAN normative power: A comparative study of Brunei and Timor-Leste - Li, Yuhong (Masyarakat, Kebudayaan dan Politik, 2025)
As the most powerful organization in Southeast Asia, ASEAN’s normative power has become an important regional order for its member countries, and its primary task is to maintain the survival of Southeast Asian countries. However, in the process of forming the normative power of ASEAN, Brunei and Timor-Leste, two smaller countries, were treated differently. Therefore, this article attempts to use Brunei and Timor-Leste as examples to explore the impact of their accession to ASEAN on the normative power of ASEAN. This article uses historical analysis methods to compare the differences in interactions between ASEAN, Brunei, and Timor-Leste. This study finds that “trust” is the key to the differences in interaction between ASEAN and Brunei and Timor Leste. The normative power of ASEAN will only come into play when member states have ‘trust’ in its identity. At the same time, the state, which is trusted by other member states, can also shape the direction and strength of norms, strengthen the integration of the community, and thus drive the expansion of the space for order. This study concluded that although economic and security factors are important, the fundamental reason for the expansion and integration of ASEAN lies in ‘trust’.